Answer:
I would love to help you but were just getting into this subject
Step-by-step explanation:
Ok im not sure the answer yet so ima work on it at the same time while im explaining it. (The answer will probably be near the end)
We can use the elimination method to eliminate y out. To do that we multiply the first equation by 3.
6x+3y=-12
Now just subtract it from the other equation.
6x+3y=-12
5x+3y=-6
***x=-6***
Usually after doing the elimination method you will have to solve for x but in this case its already solved for you. If you want to find y now you just take the first equation and fill x with -6 and solve for y.
2(-6)+y=-4
-12+y=-4
y=8
Brainliest my answer if it helps you out?
Answer:
see explanation
Step-by-step explanation:
Using the tangent and sine ratios in the right triangle EFG
tan60° =
=
=
( multiply both sides by EG )
EG × tan60° = 28 ( divide both sides by tan60° )
EG =
≈ 16.2 in ( to the nearest tenth )
--------------------------------------------------------------
sin60° =
=
=
( multiply both sides by EF )
EF × sin60° = 28 ( divide both sides by sin60° )
EF =
≈ 32.3 in ( to the nearest tenth )
Answer:
b
Step-by-step explanation: